(untitled) (Research, Society and Development, 2023)
The objective of this article is to identify and analyze the consequences of a family environment with conflicts and tensions on the learning of children and adolescents, contributing to a theoretical discussion about how emotions influence students’ learning processes, taking into account the contexts in which they are inserted. It is assumed that the understanding of factors and ecological environments that influence students emotionally can contribute to the reflection on the learning process. For the method, a theoretical research was used. We compiled articles from the databases of the Periodical Portal of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes), and literature referring to the theories that deal with this subject. Parental conflict can harm the results of children, regardless of whether parents are living together or apart, and whether they are biologically related or not related to the child, or even in adoptive families, these conflicts are capable of harming learning. Thus, this paper was able to present the impacts of parental conflict, as well as understand the idea of conflict and education and how they relate to and harm the student.